A pill for every ill?. Issue 1 (13th April 2020) - Hopping, Rachel; Ivanova, Daniela; Howe, Andrew John
Abstract : Purpose: National guidelines in the UK for emotionally unstable personality disorder and antisocial personality disorder (PD) do not recommend treatment with medication, suggesting instead psychotherapy. There is little evidence that medication has benefit from the literature. Despite this, many patients with PDs are prescribed medications. This study aims to quantify medication prescriptions within the therapeutic community for those with PD and assess if treatment led to changes in prescription. Design/methodology/approach: An audit tool was designed in Microsoft Excel; 30 most recent patients discharged from the authors' service since November 2018 were identified. Their discharge summaries were scrutinised for changes in medication comparing the beginning of treatment to the end. These were then analysed in terms of changes in class of medication and dose as well as total number of medications prescribed. Findings: In total, 31 patients' notes were scrutinised. Then, 25 patients were prescribed psychiatric medication at the start of their treatment, 24 had medications changed falling to 17 at the end of treatment. Antidepressants were the most commonly prescribed medications. By class, antidepressant prescriptions fell by 35 per cent, antipsychotics by 43 per cent, anxiolytics by 40 per cent. The prescription of mood stabilisers and Z drugs remained the same. Originality/value: The assessment of medication changes during psychotherapeutic treatment within a therapeutic community is unique in the literature. Understanding and hypothesising the dynamics involved within this process has also received little attention in research. This study highlights the potential from which further research into this neglected but pertinent area could be conducted.